A first-in-human, prospective pilot trial of umbilical cord-derived mesenchymal stem cell eye drops therapy for patients with refractory non-Sjögren's and Sjögren's syndrome dry eye disease - Di Zhang; Taige Chen; Qi Liang; Xuebing Feng; Jiaxuan Jiang; Zeying Chen; Yun Tang; Yiran Chu; Bin Wang; Kai Hu (Stem Cell Research & Therapy)
Abstract Background Patients with refractory dry eye disease (DED) often face the threat of diminished visual quality and have limited responses to existing treatments. Ocular injection of Mesenchymal stem cells (MSCs) has recently emerged as a promising new therapeutic strategy for DED. Topical eye drops are the clinical favorable choice for drug administration in DED. To date, the clinical use of MSC eye drops has not been reported in settings. This clinical trial represents a groundbreaking exploration into the preliminary therapeutic potential and safety of umbilical cord MSC eye drops for patients with refractory DED, including both non-Sjögren's dry eye (NSDE) and Sjögren's syndrome dry eye (SSDE). The study also aimed to investigate the possible underlying mechanisms. Methods In this open-label, prospective, single-arm, self-controlled trial, 11 NSDE and 5 SSDE patients received twice-daily MSC eye drops for two weeks, subsequent follow-up visits were scheduled at 4 weeks and 12 months after treatment. The primary efficacy was evaluated using the ocular surface disease index (OSDI) score, tear meniscus height (TMH), non-invasive break-up time (NIBUT), Schirmer I test (SIT), and corneal fluorescein staining (CFS) score. Secondary assessments focused on the evaluation of lipid layer, meibomian gland function, and bulbar conjunctival redness. Safety was monitored by recording adverse events (AEs) throughout the study. Changes in tear levels of interleukin-6 (IL-6), IL-17A, Mucin 5AC (MUC5AC), C–C chemokine ligand 20 (CCL20) and IL-23, along with proteomic alterations, were compared between baseline and T-week2. Results Significant clinical improvements were observed in most symptoms and signs following MSC eye drops treatment in both NSDE and SSDE patients, particularly in tear production as measured by SIT and TMH, and the alleviation of meibomian gland blockage. The therapeutic effect on OSDI, NIBUT, and the lipid layer was more pronounced in NSDE patients compared to SSDE. No serious AEs were reported during the treatment and follow-up period. Post-treatment reductions in tear levels of IL-6 and IL-17A, along with an increase in MUC5AC, further confirmed the efficacy. Tear proteomic analysis indicated that the efficacy of MSC eye drops is associated with the inhibition of inflammation caused by T helper 17 (Th17) cells in both NSDE and SSDE groups. Conclusions In this prospective exploratory clinical study, we have demonstrated that MSC eye drops might offer clinical efficacy and manageable safety in treating refractory DED for the first time, potentially bringing a new perspective on the treatment of such patients. Our research represents a preliminary exploratory endeavor, paving the way for future large-scale randomized positive-controlled trials. Trial registration: ClinicalTrials.gov, NCT05784519. Registered 28 February 2023, https://clinicaltrials.gov/study/NCT05784519 .